EFFECTIVENESS OF IMPLEMENTATION OF SUBSIDIZED HOUSING CONSTRUCTION CONTRACTS FROM THE PERSPECTIVE OF LEGAL RESPONSIBILITY: AN EMPIRICAL STUDY IN KARANGANYAR - Rhena Lastia Putri; Widi Nugrahaningsih; Rezi Rezi (Penelitian dan Pengembangan Ilmu, 2025)
Humans are social creatures who have many needs, human needs include food, clothing, and shelter. The shelter in question is a house for human habitation, so humans must be smart in choosing when they want to buy a house so that the house they live in feels comfortable, clean, safe and peaceful. The purpose of this study is to answer the problem: What is the form of legal responsibility of developers in subsidized housing construction contract disputes in Karanganyar, What factors cause subsidized housing construction contract disputes between parties in the Karanganyar area. The method used is descriptive analytical research with a sociological (empirical) juridical approach using a statutory and conceptual approach. Data were collected through in-depth interviews, documentation studies, and participatory observations, and analyzed qualitatively interactively through data reduction techniques, data presentation, and deductive conclusion drawing. Data sources used include relevant primary and secondary legal materials. Informants were selected by purposive sampling based on certain criteria according to the focus of the study. The results of the legal responsibility research of PT. Gamersi Setia Abadi in the dispute over the construction contract for subsidized housing in Karanganyar must refer to the principles of civil law and consumer protection, with the obligation to fulfill the quality of the building and compensation for losses, while the disputes that arise are generally caused by unclear contracts, defaults, and technical and non-technical errors, the resolution of which refers to the applicable provisions of construction services law.